Evidence for the Extensive Conservation of Mechanisms of Ovule Integument Development Since the Most Recent Common Ancestor of Living Angiosperms - Arnault, Gontran; Vialette, Aurélie C. M.; Andres-Robin, Amélie; Fogliani, Bruno; Gâteblé, Gildas; Scutt, Charles P. (Frontiers in Plant Science, 2018)
The ovules and seeds of most angiosperm groups are enclosed by two integuments, whose evolutionary origins are considerably separated in time, as the inner integument arose over 300 million years ago (MYA) in an ancestor of all living seed plants, while the outer integument arose, perhaps as recently as 164 MYA, in an ancestor of all living angiosperms. Studies of the model angiosperm Arabidopsis thaliana indicate that the mechanisms of development of the inner and outer integuments depend on largely different sets of molecular players. However, it was not known, in most cases, whether these differences were already present in early flowering plants, or arose later in the Arabidopsis lineage. Here, we analyse the expression patterns of integument regulators in Amborella trichopoda, the likely sister to all other living angiosperms. The data obtained indicate that regulators of the YABBY, KANADI and HOMEODOMAIN-LEUCINE ZIPPER CLASS III transcription factor families have largely conserved their integument-specific expression profiles in the Amborella and Arabidopsis lineages since the most recent common ancestor of living angiosperms. We identified only one case, involving the paralogous genes ETTIN and AUXIN RESPONSE FACTOR4, in which integument-specific expression patterns had clearly diverged between Amborella and Arabidopsis. We use the data obtained to partially reconstruct molecular mechanisms of integument development in the most recent common ancestor of living angiosperms and discuss our findings in the context of alternative hypotheses for the origin of the angiosperm outer integument.